2018
DOI: 10.3733/ca.2018a0011
|View full text |Cite
|
Sign up to set email alerts
|

Modeling guides groundwater management in a basin with river–aquifer interactions

Abstract: anagement of California's water supplies serves diverse goals. Securing the needs of urban and agricultural water customers is a key goal. Meeting environmental health, ecosystem services and stream water quality goals has also been an integral part of many California water management systems. To meet this range of goals, groundwater, soil water and surface water will need to be managed conjunctively, management will likely become more tightly linked with land use and land resources planning and management, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…This is similar to the distributed evaluation of local sensitivity analysis methodology proposed by Rakovec et al () and the use of multiple sensitivity indices (e.g., variance based and local sensitivity) by Borgonovo et al (), although less rigorous to preserve computational efficiency. Starting values for the different sensitivity runs (Table ) were selected either from a previous model calibration using the river package (RIV; Harbaugh, ; Foglia et al, ) or from within an expected range based on professional judgment. Parameters were log‐transformed and increased by 1% from their starting values for all sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…This is similar to the distributed evaluation of local sensitivity analysis methodology proposed by Rakovec et al () and the use of multiple sensitivity indices (e.g., variance based and local sensitivity) by Borgonovo et al (), although less rigorous to preserve computational efficiency. Starting values for the different sensitivity runs (Table ) were selected either from a previous model calibration using the river package (RIV; Harbaugh, ; Foglia et al, ) or from within an expected range based on professional judgment. Parameters were log‐transformed and increased by 1% from their starting values for all sensitivity analyses.…”
Section: Methodsmentioning
confidence: 99%
“…The research presented by Foglia [12] showed that there would not be a big difference in the boundary balance. However, it showed that the "exchange of water between surface water and groundwater was about three times larger in MODFLOW-RIV than MODFLOW-SFR".…”
Section: Introductionmentioning
confidence: 97%
“…In order to show new strategies to optimise the computational cost, Foglia [12] offers an exciting procedure in a case study located in Scott Valley in California. This research presents an example of environmental goals at the Scott River, which must keep a specific ecologic flow because it is an important salmon spawning habitat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations